2011
DOI: 10.1523/jneurosci.1692-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Extrasynaptic 5-HT by Serotonin Reuptake Transporter Function in 5-HT-Absorbing Neurons Underscores Adaptation Behavior in Caenorhabditis elegans

Abstract: Serotonin (5-HT)-absorbing neurons use serotonin reuptake transporter (SERT) to uptake serotonin (5-HT) from extracellular space but do not synthesize it. While 5-HT-absorbing neurons have been identified in diverse organisms from C. elegans to humans, their function has not been elucidated. Here, we show that SERT in 5-HT-absorbing neurons controls behavioral response to food deprivation in C. elegans. The AIM and RIH interneurons uptake 5-HT released from chemosensory neurons and secretory neurons. Genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 58 publications
8
85
0
Order By: Relevance
“…The members of the other pair are noted as, ADFR and ADFL (right and left amphid chemosensory neurons) and are defi ned as having two amphid sensory dendrites each. The serotonin produced by these two cell pairs has been shown to diffuse into extracellular spaces (Jafari et al, 2011). On the other hand the authors reported three adjacent ring inter neurons, RIH (unpaired), AIMR and AIML (right and left), instead, to transport serotonin (noted as serotonin reuptake transporters, SERT) controlling in this way a behavioral response to food deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The members of the other pair are noted as, ADFR and ADFL (right and left amphid chemosensory neurons) and are defi ned as having two amphid sensory dendrites each. The serotonin produced by these two cell pairs has been shown to diffuse into extracellular spaces (Jafari et al, 2011). On the other hand the authors reported three adjacent ring inter neurons, RIH (unpaired), AIMR and AIML (right and left), instead, to transport serotonin (noted as serotonin reuptake transporters, SERT) controlling in this way a behavioral response to food deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is tempting to look for homologies between the two worms. In the anterior region of C. elegans, two pairs of 5-HT-IR neurons have been described in detail by Jafari et al (2011). In C. elegans, the fi rst pair is formed by the right and left pharyngeal neurosecretory motor neurons (NSMR and NSML).…”
Section: Discussionmentioning
confidence: 99%
“…We examined the expression of bas-1, which codes for the aromatic amino acid decarboxylase that converts the TPH-1 product 5-hydroxytryptophan to serotonin (Hare and Loer 2004), the cat-4 gene, which is required to generate a co-factor for TPH-1, and the vesicular monoamine transporter encoded by cat-1 (Duerr et al 1999) (note that the serotonin reuptake transporter mod-5 is not expressed in HSN) (Jafari et al 2011). We found that expression of the entire serotonin pathway is strongly affected in the HSNs of ham-3(n1654) mutants (Figure 1, B and D).…”
Section: Phenotypic Analysis Of Ham-3 Mutants Reveals Neuronal Defectsmentioning
confidence: 99%
“…First, C. elegans allows the use of forward genetic screens to identify the proteins beyond serotonin receptors that mediate serotonin response. Second, the known synaptic wiring of the C. elegans nervous system (White et al 1986) provides the opportunity to directly test whether serotonin acts at synapses or extrasynaptically.Previous studies of C. elegans have shown that, of the precisely 302 neurons found in an adult hermaphrodite, the NSM, HSN, ADF, VC4/5, AIM, and RIH neurons contain serotonin, although the AIM, RIH, and possibly also the VC4/5 neurons do not synthesize serotonin themselves but rather take up serotonin made by the other neurons (Horvitz et al 1982;Sawin et al 2000;Jafari et al 2011). Animals with mutations in the enzymes that synthesize serotonin or in which the NSMs have been ablated are defective for the strong reduction in locomotion behavior, known as enhanced slowing, that occurs when food-deprived animals encounter food (Sawin et al 2000).…”
mentioning
confidence: 99%